2016
DOI: 10.18203/2320-6012.ijrms20164569
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of hematological parameters along with effect of chemotherapy and radiotherapy in different stages of breast cancer

Abstract: Background: Breast cancer is one of the most common malignancies found among women in India. Haematological parameters have been shown to predict severity, mortality and treatment follow-up in breast cancer patients. The aim of the study was to compare haematological parameters along with effect of chemotherapy and radiotherapy in different stages of breast cancer patients.Methods: Total 235 human subjects were taken in the study. Out of which 100 normal ages matched healthy subjects were considered as control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 16 publications
3
20
0
1
Order By: Relevance
“…Our finding is in agreement with previous study report [39] (Shrivastava, et al, 2016). However, the finding from this study is at variance with a previous report in Babylon reported by Liqaa (2014) [18] which indicated a significant increase of platelets among breast cancer subjects.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Our finding is in agreement with previous study report [39] (Shrivastava, et al, 2016). However, the finding from this study is at variance with a previous report in Babylon reported by Liqaa (2014) [18] which indicated a significant increase of platelets among breast cancer subjects.…”
Section: Discussionsupporting
confidence: 94%
“…This finding is in agreement with previous reports [36][37][38]. However, our finding is at variance with a previous report in India [39] where no significant difference was observed between TWBC counts of breast cancer subjects and controls. The discordance could be due to different testing methods used.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations